SdeK, a Histidine Kinase Required for Myxococcus xanthus Development - Pollack, Jeffrey S. (American Society for Microbiology, 2001)
The sdeK gene is essential to the Myxococcus xanthus developmental process. We reported previously, based on sequence analysis (A. G. Garza, J. S. Pollack, B. Z. Harris, A. Lee, I. M. Keseler, E. F. Licking, and M. Singer, J. Bacteriol. 180:4628–4637, 1998), that SdeK appears to be a histidine kinase. In the present study, we have conducted both biochemical and genetic analyses to test the hypothesis that SdeK is a histidine kinase. An SdeK fusion protein containing an N-terminal polyhistidine tag (His-SdeK) displays the biochemical characteristics of a histidine kinase. Furthermore, histidine 286 of SdeK, the putative site of phosphorylation, is required for both in vitro and in vivo protein activity. The results of these assays have led us to conclude that SdeK is indeed a histidine kinase. The developmental phenotype of a ΔsdeK1 strain could not be rescued by codevelopment with wild-type cells, indicating that the defect is not due to the mutant's inability to produce an extracellular signal. Furthermore, the ΔsdeK1 mutant was found to produce both A- and C-signal, based on A-factor and codevelopment assays with a csgA mutant, respectively. The expression patterns of several Tn5lacZ transcriptional fusions were examined in the ΔsdeK1-null background, and we found that all C-signal-dependent fusions assayed also required SdeK for full expression. Our results indicate that SdeK is a histidine kinase that is part of a signal transduction pathway which, in concert with the C-signal transduction pathway, controls the activation of developmental-gene expression required to progress past the aggregation stage.